Geothermal heat pump and heat engine systems : theory and practice - Chiasson, Andrew, 1966- (Wiley, 2016)
"Geothermal Heat Pump Systems: Theory and Practice comprehensively covers the theory, fundamental principles and practical applications of geothermal heat pump systems. It takes an interdisciplinary approach considering the disciplines of geoscience, thermodynamics, heat transfer, and fluid mechanics, while keeping in mind the engineering and practical constraints of the real world. The main focus of this book is geothermal heat pump applications for buildings, however the reader is introduced to the bigger picture of geothermal energy utilization, of which geothermal heat pumps is just one type. Methods and equipment used to convert stored thermal energy into useful energy are also discussed and different ground heat exchangers are considered. Geothermal Heat Pump Systems: Theory and Practice contains end of chapter exercise problems and discussion questions and is accompanied by a website hosting practical design software tools that allow the solution of complex, real problems. It also includes presentation files with lecture slides."-- Provided by publisher
Keywords: Ground source heat pump systems.; Heat pumps -- Thermodynamics.; Heat-engines -- Thermodynamics.; elektronické knihy; electronic books